2013
DOI: 10.5937/fizkul1302103d
|View full text |Cite
|
Sign up to set email alerts
|

Morphological model of the population of working-age women in Belgrade measured using electrical multichannel bioimpedance model: Pilot study

Abstract: , фитнес скор 73.23±6.75 индексних бодова. Из добијених резултата може се закључити да актуелни морфолошки статус испитиваних жена делимично одговара нормално ухрањеном типу. БМИ и заступљеност телесних масти су имали готово граничне вредности, према гојазности. Забележен је врло висок проценат жена у категорији предгојазних и гојазних према БМИ (40%) и ПСМ (36%).Кључне речи: ТЕЛЕСНИ САСТАВ / БИОИМПЕДАНЦА / ЖЕНЕ / МАСНО ТКИВО / БМИ Коресподенција са: Mарина Ђорђевић-Никић, Универзитет у Београду, Факултет спор… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…When analyzing the results of working women aged 35.2 years [4] it can be concluded that the prevalence of underweight and obese was 2.14 (9.64 vs 30.27 %) and 2.22 (3.13 vs 10.09 %) higher in relation to the results of this study. Wilks' lambda = 0.122, p = 0.000, ɳ 2 = 0.409 Wilks' lambda = 0.347, p = 0.000, ɳ 2 = 0.232 ANOVA F = 29.59, p = 0.000 F = 30.33, p = 0.000 F = 508.44, p = 0.000 F = 31.46, p = 0.000 F = 157.7, p = 0.000 F = 138.0, p = 0.000 F = 157.6, p = 0.000 F = 173.9, p = 0.000 Legend: * p = 0.000, statistically significant differences between all groups; # p = 0.000, Overweight I vs. all other BMI subgroups except Overweight II, Obese I, II and III; § p = 0.000, Overweight II vs. all other BMI subgroups, except Overweight I, Obese I, II and III; ¥ p = 0.005, Obese I vs. all other BMI subgroups, except Overweight I and II, Obese II and III; £ p = 0.001, Obese II vs. all other BMI subgroups, except Overweight I and II, Obese I and III; † p = 0.001, Obese III vs. all other BMI subgroups, except Overweight I and II, Obese I and II; @ p = 0.000, Normal range I vs. all other BMI subgroups, except Obese III; & p < 0.05, Normal range II vs. all other BMI subgroups, except Overweight II and Obese III; © p = 0.005, Obese III vs. all other BMI subgroups, except Underweight Допсай М., Джорджевич-Никич М.,…”
Section: физиологияsupporting
confidence: 48%
See 2 more Smart Citations
“…When analyzing the results of working women aged 35.2 years [4] it can be concluded that the prevalence of underweight and obese was 2.14 (9.64 vs 30.27 %) and 2.22 (3.13 vs 10.09 %) higher in relation to the results of this study. Wilks' lambda = 0.122, p = 0.000, ɳ 2 = 0.409 Wilks' lambda = 0.347, p = 0.000, ɳ 2 = 0.232 ANOVA F = 29.59, p = 0.000 F = 30.33, p = 0.000 F = 508.44, p = 0.000 F = 31.46, p = 0.000 F = 157.7, p = 0.000 F = 138.0, p = 0.000 F = 157.6, p = 0.000 F = 173.9, p = 0.000 Legend: * p = 0.000, statistically significant differences between all groups; # p = 0.000, Overweight I vs. all other BMI subgroups except Overweight II, Obese I, II and III; § p = 0.000, Overweight II vs. all other BMI subgroups, except Overweight I, Obese I, II and III; ¥ p = 0.005, Obese I vs. all other BMI subgroups, except Overweight I and II, Obese II and III; £ p = 0.001, Obese II vs. all other BMI subgroups, except Overweight I and II, Obese I and III; † p = 0.001, Obese III vs. all other BMI subgroups, except Overweight I and II, Obese I and II; @ p = 0.000, Normal range I vs. all other BMI subgroups, except Obese III; & p < 0.05, Normal range II vs. all other BMI subgroups, except Overweight II and Obese III; © p = 0.005, Obese III vs. all other BMI subgroups, except Underweight Допсай М., Джорджевич-Никич М.,…”
Section: физиологияsupporting
confidence: 48%
“…If we make a comparison of the results between the 4D relative model in relation to working-age Belgrade women population and BU female students, it can be argued that the highest level of changes in the body composition has been established in relation to body fat (PBF 24.34 vs 30.32 %), where adult females have 16.42 % higher PBF in the body, while at the same time they have 8.02 %, 7.31 % and 7.02 % less minerals, protein and TBW, respectively [4].…”
Section: исследование состава тела хафизова а и др и распространеннmentioning
confidence: 99%
See 1 more Smart Citation
“…Overweight and obesity are defined as the excessive accumulation of fat and represent a health risk [1] . Obesity is one of the most dangerous challenges among the developed countries [2] .…”
Section: Introductionmentioning
confidence: 99%